The Influence of Emotional Intelligence on Resilience in Working Professionals: A Correlational Study - Garg, Rahul (Journal of Social Science and Humanities, 2025)
Emotional intelligence can be defined as the ability to perceive emotions, to access and generate emotions so as to assist thought, to understand emotions and emotional knowledge, and to regulate emotions reflectively so as to promote emotional and intellectual growth. Resilience is the ability to withstand or recover quickly from difficult situations. Research has shown that emotional intelligence can influence an individual’s resilience. The present study aimed to study the influence of emotional intelligence on resilience among working professionals. The Schutte Self-Reported Emotional Intelligence Test (SSEIT) and Brief Resilience Scale were used in the study. The selected sample consisted of 70 working professionals (38 male and 32 female) selected from Tier-I cities (age range: 21-40 years). Descriptive statistics and a two-way ANOVA were performed to analyze the data. The findings showed that there is a significant difference between the resilience of people with varying levels of emotional intelligence. Furthermore, no significant influence of gender on resilience was found.